Fearful-Avoidant Attachment: A Specific Impact on Sexuality?. Issue 6 (18th August 2019) - Favez, Nicolas; Tissot, Hervé
Abstract: In this study, we investigated sexual outcomes in individuals presenting fearful-avoidant attachment, that is, those who have both high avoidant and anxious attachment tendencies (reluctant to engage in a close relationship and a dire need to be loved by others). A community sample of men and women ( N = 600; 25–45 years) completed self-reported questionnaires related to attachment, sexuality, and control variables. Results showed that fearful avoidance is predictive of (a) more sexual partners in individuals during their lifetime and (b) greater sexual compliance. These effects were true for women as well as for men.